Environmental consciousness amongst indigenous youth in Kenya: The role of the Sengwer religious tradition - King'asia Mamati (AOSIS, 2021)
Environmental destruction has contributed to climate change, a contemporary threat to the survival of the human race. Currently, many young people across the world are increasingly and actively involved in climate action, because of the realisation that climate change will disproportionately affect them. Kenya is adversely affected by climate change, with erratic and unpredictable rainfall patterns now being the norm. Given that the youth make up a large segment of the Kenyan population, they are well placed to contribute efficaciously to combating climate change. This article relied on both primary and secondary sources of data. Interviews, participant observations, focus group discussions, articles, books and archival material were used to generate data. Purposive and snowball sampling techniques were used to get key informants. Data were analysed thematically as per the topic under study. The article focuses on how the Sengwer indigenous community created environmental awareness and utilised their epistemological approaches to ensure a conscious mindset amongst the youth on the sustainability of the environment. In this article, we argue that the complex social systems that have religious underpinnings in traditional society play a critical role in ensuring that young people are environmentally conscious. Religion facilitates knowledge acquisition amongst the youth and shapes their understanding and consciousness of the environment. The findings indicate that indigenous communities had an effective system of ensuring that young people are conscious of their environment.